2006
DOI: 10.1007/s00468-006-0088-9
|View full text |Cite
|
Sign up to set email alerts
|

Interannual growth response of Norway spruce to climate along an altitudinal gradient in the Tatra Mountains, Poland

Abstract: Ring-width chronologies of Picea abies (L.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
59
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 40 publications
15
59
3
4
Order By: Relevance
“…Significantly lower growth of provenances originally from the altitude above 800 m a.s.l. was documented on our experimental site (Table 2), which corresponds with other studies (Šindelář 1994;Savva et al 2006), concerning stem volume (Oleksyn et al 1997) or biomass (Modrzyński, Eriksson 2002). At the same time documented that (Slovakian) spruce provenances generally responded positively (increased height and volume growth) to transfer to lower altitudes (warmer and drier climates).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Significantly lower growth of provenances originally from the altitude above 800 m a.s.l. was documented on our experimental site (Table 2), which corresponds with other studies (Šindelář 1994;Savva et al 2006), concerning stem volume (Oleksyn et al 1997) or biomass (Modrzyński, Eriksson 2002). At the same time documented that (Slovakian) spruce provenances generally responded positively (increased height and volume growth) to transfer to lower altitudes (warmer and drier climates).…”
Section: Discussionsupporting
confidence: 91%
“…The extremity of the stand is probably quite an important factor (Kapeller et al 2012) and increment (of European provenances) responds to climatic conditions markedly only on the extreme sites (Mäkinen et al 2002). It was also confirmed by Savva et al (2006), who reported for Norway spruce at high altitudes a higher correlation between summer temperatures and radial increment (rather than height increment). Since in our experiment the highest altitude of the provenance location was 1,600 m a.s.l.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Tree-ring width is commonly related to climate in both the previous year and current year (Bräuning 1999;Takahashi et al 2005;Savva et al 2006), which was also verified in this study. Generally, TRW was negatively associated with temperatures in the prior winter and the months before the growing season at all elevations (Fig.…”
Section: Discussion Chronology Evaluationsupporting
confidence: 83%